Psychological Empowerment on Innovative Behavior with Transformational Leadership Style as Moderator Variable - Yoga Priyatama; Farid Soleh Nurdin; Irfan Fahmi (Da'wa Faculty of Islamic State University Salatiga, 2022)
State-Owned Enterprises (BUMN) is a company that has a role as an agent of value crator and agent of development. So what must be done is to improve the performance of BUMN, restructure BUMN and establish new BUMN. In achieving its goals, this role must be realized by carrying out a high innovation from every individual who is in a company. In terms of increasing Psy, an application of psychological empowerment is needed in the company and moderated by leaders who have a Transformational Leadership Style. This study uses a quantitative research method using a structural equation model (Structural Equation Model-Partial Least Square/SEM-PLS). Respondents in this study amounted to 35 employees with certain criteria. The results of the study show that there is an influence on Psychological Empowerment on Innovative Behavior, while the magnitude of the influence is 0.523. There is also the influence of Transformational Leadership Style on Innovative Behavior with a magnitude of 0.495. As a moderating variable, Transformational Leadership Style can also moderate the effect of Psychological Empowerment on Innovative Behavior with a score of 0.149.